Sade - Warman, C (Voltaire Foundation, 2017)
Sade’s personal fate has too long encouraged critics to concentrate on his personal isolation and personal revolt. Extraordinary as his life was, the light that it throws on his work casts into shade the intellectual context that was much more important to its generation than his actual experience. This book is about how Sade took a pure version of eighteenth-century materialism and rendered it into an even purer form of pornography. The eternal yet unequal clashing of atomic bodies became the endless torture of human ones. It traces the intellectual genealogy that links Sade to his materialist forebears (d’Holbach, Condillac, Buffon, Diderot, La Mettrie, Robinet, Delisle de Sales) and shows how the germs of cruel pleasure were already present in elements of their work, as much in their rhetoric and stylistics as in their arguments. Sade, aided by his grounding in the interpretative techniques of illicit clandestine and libertine literature, read them attentively and developed their presentation as well as their content into a flawlessly logical and self-referential system. Thus the arrogant philosopher (the author / the libertine) did not just mouth his cruel positions but enacted them, proving the behaviour of matter as he/she did so. This reading of Sade’s work refers its principal elements – shape, style and contents – back to the hardcore of materialism, offering an account which, while not making it more tolerable, renders it at once more accessible and more comprehensible. Acknowledgements Abbreviations Introduction 1. Sade and materialism since 1945 2. Sensationist materialism: system and technique 3. Persuasion: the philosophe’s rhetorical profile 4. Sade’s system 5. ‘Comme fondu dans le fonds commun’: clandestine and libertine ingredients in the Sadean melting pot 6. Literality 7. The Drama of matter Bibliography Index